Carbon fiber-reinforced epoxy with 100% fiber recycling by transesterification reactions - Wu, Jianqiao; Pan, Ying; Ruan, Ziyi; Zhao, Ziji; Ai, Jing; Ban, Jinghai; Jing, Xianghai (Frontiers in Materials, 2022)
Carbon fiber (CF)-reinforced epoxy is the most commonly used advanced composite with high performance. However, these composites usually face intractable disposal problems in their lifecycles, due to the stable cross-linked network structures of epoxy. To address this dilemma, this work proposes a facile yet efficient strategy for recycling carbon fibers from traditional carbon fiber-reinforced epoxy composites using epoxy–anhydride systems as a matrix. Diglycidyl ester of aliphatic cyclo (DGEAC) and methylhexahydrophthalic anhydride (MHHPA) were used as matrix, while T300 woven carbon fiber was used as reinforcement, to construct the composites CF/DGEAC/MHHPA. The epoxy matrix exhibited a high glass transition temperature (Tg = 126°C), high decomposition temperature (Td5 = 300°C), and good solvent resistance. By using 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD) as a catalyst, the DGEAC/MHHPA networks could be degraded completely in ethylene glycol (EG) at 180°C within 6 h because of transesterification reactions between EG and the networks. Taking advantage of this result, a fiber recycling process was developed for carbon fiber composites, where the cross-linked networks of epoxy could be degraded with 100% carbon fiber recycling. Furthermore, the recycled carbon fiber maintained nearly 100% similarity in surface microscopic morphology and chemical structure compared with virgin carbon fiber. This work proposes a simple and efficient strategy for recycling carbon fiber from traditional high-performance composites, offering a convenient concept for the cyclic utilization of advanced composites.